Learning Style of Grade V Students At Elementary Schools In Blitar - Bintartik, Lilik; Yuniawatika, Yuniawatika; Untari, Esti (Faculty of Education Universitas Negeri Malang, 2018)
The purpose of this study is to identify learning styles of grade V students at elementary schools in Blitar. This is a quantitative study using descriptive methods involving grade V students at elementary schools in Blitar Sample of 199 students were selected using simple random sampling. Questionnaires were used to gather the data, and analyzed employing descriptive statistical techniques. Results showed that the auditorial learning style was used dominantly by all female and male students. Keywords: students, teachers, teaching, learning styles.